Body image dissatisfaction in adolescents: Comparison with physical activity, teasing and social support - Gonzaga I.* (2021)
© The Author(s) 2019.This study aimed to compare the adolescents’ body dissatisfaction with physical activity, teasing during physical activity and social support. Participants were 938 Brazilian adolescents aged 15–19 years. Study variables were investigated through questionnaires. There was no difference in body dissatisfaction among adolescents who practiced and did not practice physical activity, but among the former, those who had been teased had greater body dissatisfaction. Also, adolescents who had a relative or friend to talk, in addition to giving and receiving affection, more frequently, presented lower body dissatisfaction. Stratifying the sample by gender, the results were similar in females but were not significant in males.